Kansas agricultural education teacher priority differences among early-, mid-, and late-career teachers and among traditionally and alternatively certified teachers - Lehmann, Emma (My University, 2025)
Mentoring programs have been and continue to be used heavily for beginning Agricultural Education Teachers in assisting them through the ups and downs of teaching. However, it is becoming increasingly important to continue mentorships for teachers past their beginning years as there are still challenging aspects to the career. Due to little knowledge of mentorship programs for mid- and late- career ag teachers it is imperative to understand their needs and priorities of their professional and personal lives. The purpose of this study was to determine the priorities of early-, mid- and late-career Kansas Ag Teachers as well as those who are traditionally and alternatively certified. Forty Kansas Agriculture Teachers completed and turned in an agriculture teacher priorities instrument. Teachers within one to five years of teaching are considered early career teachers, their most important and high importance priorities were teaching local daily classes, local FFA activities, CDEs, family life, and designated family time of one-and-a-half days. While mid-career teachers in years six to fifteen place their most important and high importance priorities in daily lessons, local and above FFA activities, and being good neighbors. As for late-career teachers in years sixteen plus their most and high importance priorities included daily lessons, local FFA activities, participating in professional development, developing course outlines and calendars, family life, and designated family time of one-and-a-half days. Overall, daily classes, local FFA activities, family life, and dedicating one-and-a-half days to family time was determined the most important or a high importance priority for all career stages of teachers. Traditionally certified teachers determine daily lessons, local and above FFA activities, CDEs, and family time as their most important and high importance priorities. While most important and high importance priorities of alternatively certified teachers were daily lessons, professional development, family time, designating one-and-a-half days to family time, and having a second job or employment. Data shows that traditionally and alternatively certified teachers agreed daily classes, personal leisure time, family time, dedicating one-and-a-half days of family time, and having a second means of income or employment were the most important or high importance priority items. This information will assist in developing and altering mentoring programs and professional development opportunities for teachers in various stages and on different paths of certification within their professional career.
Keywords: Agricultural education; Priorities; Early-career teachers; Late-career teachers; Alternatively certified teachers; Traditionally certified teachers